Potential Benefits of RCEP on the Philippines: Accelerating Recovery Through Trade and Other Economic Opportunities - Cororaton, Caesar (Animo Repository, 2021)
The Philippines, as a member of ASEAN, is part of the RCEP, which is the world’s largest trading block in terms of population and GDP. RCEP was signed on November 15, 2020, by 15 member countries. This policy note discusses the potential effects of RCEP on the Philippines. Using a global CGE model calibrated to the most recent GTAP 10 database, the results indicate that the Philippines will benefit from higher exports, lower consumer prices, higher factor prices, and factor incomes of households. Among the Philippine sectors, the largest positive effects are observed in electronic equipment. Interestingly, the impact on the agriculture-food sector is also notable.